Assessment of Liposomal Formulations and Biological Activities of Eggplant Glycoalkaloids - Tatlıdil, Engin; Frary, Anne; Tatlıdil, Engin (Izmir Institute of Technology, 2019)
Billions of dollars are spent every year in the world for cancer treatments and research. In recent years, bioactive compounds are being tested as promising therapeutics. Among these compounds, eggplant glycoalkaloids: solasonine and solamargine are known to be effective against skin cancer and diseases. However, these compounds are water insoluble. This reduces transdermal drug delivery and the efficacy of solasonine and solamargine. Nanocarriers are used for transdermal drug delivery of water insoluble molecules. In this study, liposomes were used as nanocarriers to increase drug delivery of solasonine and solamargine. In the first stage of the study, empty liposomes produced from four different lecithin types with hydration temperatures of 40°C, 45°C and 50°C were evaluated according to their physical, chemical stability and drug loading capacity criteria at three different storage temperatures (4°C, 25°C, 37°C). The liposome formulation which was most suitable for the continuation of the study was determined. In the second stage of the study, solasonine and solamargine loaded liposomes were produced according to the formulation determined in the first stage and these liposomes were evaluated according to their physical, chemical stability, zeta potentials and drug leakage rate criteria for 3 months and it was determined that the drug loaded formulation was stable during the monitoring process. Furthermore, the release profiles of the drugs in different release media were determined and also the efficacy of the free and encapsulated states of solasonine and solamargine were tested in HaCaT and SCC-25 cell lines and IC50 values were determined.

Dünyada her yıl kanser tedavileri ve araştırmalarına milyarlarca dolar harcanmaktadır. Son yıllarda, biyoaktif bileşikler umut verici terapötikler olarak test edilmektedir. Bu bileşikler arasında patlıcan glikoalkaloidleri: solasonin ve solamarjinin cilt kanseri ve hastalıklara karşı etkili olduğu bilinmektedir. Bununla birlikte, bu bileşikler suda çözünmezdir. Bu durum, transdermal ilaç dağıtımını ve solasonin ve solamarjinin etkinliğini azaltmaktadır. Suda çözünmeyen moleküllerin transdermal ilaç iletimi için nanotaşıyıcılar kullanılmaktadır. Bu çalışmada solasonin ve solamarjinin ilaç iletimini arttırmak için nanotaşıyıcı olarak lipozomlar kullanılmıştır. Çalışmanın ilk aşamasında 4 farklı lesitin tipinden 40°C, 45°C ve 50°C hidrasyon sıcaklıkları ile üretilen boş lipozomlar 3 farklı saklama sıcaklığında (4°C, 25°C, 37 °C) fiziksel, kimyasal stabiliteleri ve ilaç yükleme kapasiteleri kriterlerine göre değerlendirilip çalışmanın devamı için en uygun olan lipozom formülasyonu belirlenmiştir. Çalışmanın ikinci aşamasında ilk aşamada belirlenen formülasyona göre solasonin ve solamarjin yüklü lipozomlar üretilmiş bu lipozomlar 3 ay boyunca fiziksel, kimyasal stabiliteleri, zeta potensiyelleri, ilaç kaçak oranı kriterlerine göre değerlendirilmiş ve ilaç yüklü formülasyonun gözlem süreci boyunca stabil kaldığı belirlenmiştir. Ayrıca ilaçların farklı salım ortamlarındaki salım profilleri belirlenmiş ve aynı zamanda solasonin ve solamarjinin serbest ve enkapsüle hallerinin etkinliği HaCaT ve SCC-25 hücre hatlarında denenmiş ve IC50 değerleri tespit edilmiştir.
Patlıcan Glikoalkaloidlerinin Lipozomal Formülasyonlarının ve Biyolojik Aktivitelerinin Değerlendirilmesi
Thesis (Master)--Izmir Institute of Technology, Molecular Biology and Genetics, Izmir, 2019
Includes bibliographical references (leaves: 47-55)
Text in English; Abstract: Turkish and English
Keywords: Drug delivery; Eggplant glycoalkaloids; Solasonine; Solamargine; Nanocarriers